Utilization of anthocyanin-rich flour from Balatinaw black rice (Oryza sativa L.) for the development of functional Filipino pan bread (pandesal) - Gamboa, Mark Andrie T. (College of Home Economics, University of the Philippines Diliman, 2023)
Balatinaw is a heirloom rice variant native from Cordilleras which is considered underutilized due to the preference over white rice. This is why the study utilized Balatinaw black rice flour in developing functional Filipino pan bread (pandesal). The effect of different black rice flour (BRF) to all-purpose flour ratio (10:90, 25:75, 50:50, 5:25, 90:10) on the consumer acceptability and physico-chemical properties [instrumental color (L*, a*, b*), and moisture content] of black rice pandesal (BRP) was investigated. The BRP prototypes were subjected to sensory evaluation via consumer acceptability. Results showed all samples were found to be generally acceptable based on five (5) attributes (appearance, color, aroma, flavor, mouthfeel). Pearson correlation analysis also showed significant correlation (p<0.05) of overall acceptability with appearance, color, flavor and mouthfeel. In terms of instrumental color, the increasing BRF content resulted in the decrease of L* (lightness) of the samples, increase in a* (towards red), and decrease in b* (towards blue). Comparing the sample's interior and exterior, the exterior was found to have lower L* values, higher a* values, and lower b* values. Moisture content also decreased with increasing BRF content. Sample B (25:75), the most preferred sample, was found to have an 8.74 ± 0.07% protein content. The study gives additional insights in maximizing the use of BRF to increase nutritive value and improve functional properties in bakery applications. Moreover, this study also provides baseline data for BRF as an alternative flour substitute in future product development studies.